Determining Factors for Independent Walking in Patients Undergoing Cardiovascular Surgery: Differences between Coronary Artery Bypass Grafting, Heart Valve Surgery, and Aortic Surgery - Yui Sakamoto (MDPI AG, 2021)
Physical deconditioning often occurs during the acute phase after cardiovascular surgery, and unassisted walking is required to achieve independence, to manage cardiac diseases, and to prevent recurrences. This study aims to investigate the characteristics of independent walking after cardiovascular surgery. We conducted a retrospective cohort study in patients who underwent cardiovascular surgeries (total of 567 patients): 153 in the coronary artery bypass grafting (CABG) group, 312 in the heart valve surgery group, and 102 in the aortic surgery group. We evaluated the effect of each surgery group on the cardiac rehabilitation (CR) progression. The factors associated with independent walking were age, renal diseases, intensive care unit (ICU) length of stay, and post-operative respiratory complications in the CABG group. In the heart valve surgery group, the factors were New York Heart Association functional classification, renal and respiratory diseases, ICU length of stay, duration of mechanical ventilatory support, and post-operative cardiovascular and respiratory complications. In the aortic surgery group, these were ICU length of stay and acute kidney injury. The CR progression in patients who underwent aortic surgery was significantly longer than those who underwent CABG and heart valve surgery (p < 0.001). New intervention strategies are needed for patients with prolonged ICU stays.